Sonochemical coating as an effective method of polymeric nonwovens functionalization. Issue 11 (22nd July 2019) - Kołbuk, Dorota; Urbanek, Olga; Denis, Piotr; Choińska, Emilia
Abstract: A surface of polymeric nonwovens may be coated with various types of nanoparticles for medical applications, filtration, and so forth. However, quite often methods used for surface modification are difficult to scale up or are not applicable for polymers. In this article, we present one‐step process enabling nonwovens functionalization. Poly(l ‐lactide‐ co ‐glicolide) (PLGA) nonwovens were prepared by electrospinning process and coated with hydroxyapatite nanoparticles (HAp) using ultrasonic processing. The effect of the process was evaluated with various techniques. HAp layer was successfully attached without loss of structural properties of HAp or PLGA nonwovens. The analysis confirmed the decrease of hydrophobicity of coated nonwoven, as well as its biocompatibility, making this material valuable from the perspective of medical applications. The sonochemical functionalization of polymeric nonwovens may be considered as an effective and economic method, enhancing surface properties of electrospun nonwovens for various applications.